Depression and its correlation with social support and health-promoting lifestyles among Chinese university students: a cross-sectional study. Issue 7 (5th July 2021) - Tang, Zaili; Feng, Shuidong; Lin, Jing
Abstract : Objectives: To investigate the prevalence of depression in college students and determine how social support and healthy lifestyle factors are associated with depression in this population. Design: A cross-sectional design. Setting: A comprehensive university in Changsha, Hunan, South China. The study was conducted from May to June 2019. Participants: A total of 541 students at the comprehensive university. Primary and secondary outcome measures: The Zung Self-Rating Depression Scale, Social Support Rating Scale and Health-Promoting Lifestyle Profile-II (HPLP-II) were used to evaluate depression, social support and lifestyles, respectively, and analyse the mutual relationships among them. Results: Among the 541 participants, 161 (29.8%) experienced depressive symptoms, and there were significant gender-related and academic discipline-related differences in self-rated depression. The average social support score was 38.06 (38.06±7.52). The average HPLP-II score was 71.09 (71.09±11.47). A monofactor analysis showed that depression was correlated with social support and a healthy lifestyle. As demonstrated by logistic regression analysis, being a woman (OR=2.613, 95% CI: 1.541 to 4.43), inadequate social support (OR=0.912, 95% CI: 0.877 to 0.948), poor nutrition (OR=0.87, 95% CI: 0.775 to 0.977) and lack of self-actualisation (OR=0.644, 95% CI: 0.572 to 0.724) were significantly correlated with depression. Conclusions: Owing to the high prevalence of depression among Chinese university students, educational institutions must take measures such as providing compulsory mental health education courses and improving the psychological counselling services available to students.